Group-Invariant Solutions and Conservation Laws of One-Dimensional Nonlinear Wave Equation (Journal of Nonlinear Modeling and Analysis, 2024)
Based on classical Lie symmetry method, the one-dimensional nonlinear wave equation is investigated. By using four-dimensional subalgebras ofthe equation, the invariant groups and commutator table are constructed. Furthermore, optimal system of the equation is obtained, and the exact solutionscan be gained by solving reduced equations. Finally, a complete derivation ofthe conservation law is given by using conservation multipliers.